Analisis Risiko Penyebaran Covid-19 Melalui Fasilitas dan Kegiatan di Universitas Sahid Menggunakan Metode HIRADC - Siti Azahra I. Atmariyani; Tatan Sukwika; Ninin Gusdini (Journal of Applied Management Research, 2022)
Coronavirus Disease 19 (COVID-19) is an infectious disease caused by acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Facilities and activities at Sahid University Jakarta have the potential to spread Covid-19, so an assessment of the risk and hazard control level is carried out. This study aims to identify activities that have the potential to spread COVID-19, assess the level of risk of spreading COVID-19, and determine controls for the risk of spread and transmission at Sahid University. The probability and impact assessment method for 16 activities with 34 variables uses the Hazard Identification, Risk Assessment, and Determining Control (HIRADC) method. Processing the data to obtain results, variable risk 15%, high, low risk 6%, and 79% moderately high risk. The study's conclusion found that the main activities that potentially spread the Covid-19 virus are face-to-face lectures, administration, finance, and laboratory learning. Measures to control the risk of transmission through engineering and reorganization of work, administrative controls, and use of PPE. The research suggests that each need be aware to remind each other and carry out obligations in the health protocol for the sake of realizing a Covid-19 free environment at Sahid University Jakarta and its surroundings.